Ethics of Organizational Leadership in Islamic Perspective - Muhammad Aziz Mahyuti; Nadya Ferisca Siregar; Khoiril Ardi (Journal of Global Islamic Economic Studies, 2024)
Organization is an important element in students. Behavior and ethics are formed by how the organization runs according to the existing vision and mission. Leadership in the organization is an important factor in the success of the organization. Problem solving in the organization is the responsibility of all members of the organization. Good leadership will guide its members to be more integrity in finding solutions to existing problems. Ethics in Islam are norms and teachings that have been taught by Islamic teachings. Organizational leadership according to Islam will be discussed in this article. This study uses a qualitative method in the form of a literature review. Based on the results obtained by the author, that the ethics of organizational leadership according to the Islamic perspective have the meaning of goodness (al-khair), happiness (al-sa'adah), and virtue (al-fadilah). All of which will form a good and integrity organization in the future.